Art and mentalizing in early intervention psychosis: rationale and therapist insights on a new psychoeducational course - Parkinson, Sarah; Cole, Bethany; Trevelyan, Clare (Frontiers in Psychiatry, 2024)
In this paper, we explore the rationale for a combined art therapy and mentalization-based treatment (MBT) group course for those experiencing a first episode of psychosis (FEP). We discuss the theoretical background for how art and MBT theory can help us better understand and work with groups of individuals experiencing FEP, particularly focusing on avoidance and insecure attachment styles. We outline the delivery of a ten-week psychoeducational Art MBT course within an Early Intervention in Psychosis (EIP) Service and discuss our experiential insights into this new modality as co-therapists. We conclude by proposing that art therapy and mentalizing practice together offer an accessible, useful and practical group structure for EIP services, which could improve individuals’ mentalizing capacity and overall social functioning.